Gender, skin color, and household composition explain inequities in household food insecurity in Brazil. - Lissandra Amorim Santos; Rafael Pérez-Escamilla; Camilla Christine de Souza Cherol; Aline Alves Ferreira; Rosana Salles-Costa (Public Library of Science (PLoS), 2023)
It is well known that female-headed households (FHHs) are more likely to experience food insecurity (FI) than male-headed households (MHHs), however there is a dearth of evidence on how gender intersects with other social determinants of FI. Thus, this paper investigated changes in the prevalence of household FI in Brazil from 2004 to 2018 by the intersection of gender, race/skin color and marital status of the household reference person. Data from three cross-sectional nationally representative surveys that assessed the status of FI using the Brazilian Household Food Insecurity Measurement Scale were analyzed (N2004 = 107,731; N2013 = 115,108, N2018 = 57,204). Multinomial logistic regression models were used to examine the relationship between profiles of gender, race/skin color, marital status of the head of the household with household FI stratified by the presence of children <5 years of age. Over time, FHHs had a higher prevalence of mild and moderate/severe FI than did households headed by men. Food security prevalence increased from 2004 to 2013 and decreased between 2013 and 2018 for households headed by men and women. In 2018, households headed by black/brown single mothers with children < 5 years of age were at the highest FI risk. The probability of reporting moderate/severe FI in these households were 4.17 times higher (95% CI [2.96-5.90]) than for households headed by married white men. The presence of children in the household was associated with a higher probability of moderate/severe FI, especially for households headed by black/brown individuals regardless of the reference person's gender. The results suggest that gender inequities combined with darker skin color and the presence of children at home potentiate the risk of moderate/severe FI. Policy makers need to consider the principles of intersectionality when investing in codesigning, implementing, evaluating, and scaling up evidence-based programs to reduce FI.